2016
DOI: 10.7150/jca.15656
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Systemic Therapy and Recurrence Pattern on Survival Outcome after Radiofrequency Ablation for Colorectal Liver Metastases

Abstract: Background: Most patients undergoing radiofrequency ablation (RFA) of colorectal liver metastasases (CLM) develop disease recurrence, but little is known about the effect of recurrence patterns and/or systemic therapy on outcome. In this study, we examined the recurrence patterns and survival after systemic therapy plus RFA in patients with unresectable CLM without extrahepatic disease. The aims were to analyze the effect of recurrence patterns on survival and to assess the relative benefit contributed by syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In the present study, chemotherapy itself presented no positive role in reducing the rate of LTP, but the response to chemotherapy was a strong independent predictor for LTP. Similar results have been reported in the literature on RFA [36]. CRLM with PR may present with smaller sizes and relatively little blood supply, which is conducive to achieving adequate safety margins for ablation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, chemotherapy itself presented no positive role in reducing the rate of LTP, but the response to chemotherapy was a strong independent predictor for LTP. Similar results have been reported in the literature on RFA [36]. CRLM with PR may present with smaller sizes and relatively little blood supply, which is conducive to achieving adequate safety margins for ablation.…”
Section: Discussionsupporting
confidence: 87%
“…CRLM with PR may present with smaller sizes and relatively little blood supply, which is conducive to achieving adequate safety margins for ablation. Meanwhile, chemotherapy may eradicate micrometastases surrounding CRLM [7,36], which may help to prevent LTP following ablation.…”
Section: Discussionmentioning
confidence: 99%
“…RFA is currently regarded as a safe and effective treatment for lung primary and metastatic tumors, especially for these inoperable patients [ 3 , 20 ]. It has key advantages, for example, precise treatment effect, high safety, and small trauma, which have become an important part in nonsurgery treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence after RFA could in uence treatment and survival for CLM [20]. Thus, a better understanding of recurrence was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…There were several studies investigated the coloration KRAS gene and recurrence after RFA for CLM [18,19]. A recent report showed that recurrence after RFA could in uence the treatment and survival of CLM patients [20].Therefore, A better comprehension of correlation may improve decision-making about pre-, intra-, and post-RFA.…”
Section: Introductionmentioning
confidence: 99%